Between Interactions and Aggregates: The PolyQ Balance. (13th November 2021) - Mier, Pablo; Andrade-Navarro, Miguel A
Abstract: Polyglutamine (polyQ) regions are highly abundant consecutive runs of glutamine residues. They have been generally studied in relation to the so-called polyQ-associated diseases, characterized by protein aggregation caused by the expansion of the polyQ tract via a CAG-slippage mechanism. However, more than 4, 800 human proteins contain a polyQ, and only nine of these regions are known to be associated with disease. Computational sequence studies and experimental structure determinations are completing a more interesting picture in which polyQ emerge as a motif for modulation of protein–protein interactions. But long polyQ regions may lead to an excess of interactions, and produce aggregates. Within this mechanistic perspective of polyQ function and malfunction, we discuss polyQ definition and properties such as variable codon usage, sequence and context structure imposition, functional relevance, evolutionary patterns in species-centered analyses, and open resources.